Silver nanoparticles are lethal to the ciliate model Tetrahymena and safe to the pike silverside Chirostoma estor; Experimental Parasitology; Vol. 209 - Fuentes-Valencia M. A.; Fajer-Avila E. J.; Chavez-Sanchez M. C.; Martinez-Palacios C. A.; Garibo D. Diana; Susarrey-Arce A. Arturo; Bogdanchikova N. Nina; Martinez-Chavez C. C.; Junqueira-Machado G.; Lara H. H. Humberto Herman; Raggi L.; Gomez-Gil B.; et al. (2020, 2020)
Title screen